2020
DOI: 10.1021/acs.jpcc.0c01559
|View full text |Cite
|
Sign up to set email alerts
|

When are Antiaromatic Molecules Paramagnetic?

Abstract: Magnetizabilities and magnetically induced current densities have been calculated and analyzed for a series of antiaromatic cyclo[4k]carbons (k=2-11), iso [n]phlorins (n=4-8), expanded porphyrinoids and meso-meso, β-β, β-β triple linked porphyrin and isophlorin arrays. The cyclo[4k]carbons with k=2-6 are predicted to be closed-shell paramagnetic molecules due to the very strong paratropic ring current combined with its large radius.Larger cyclo[4k]carbons with k=6-11 are diamagnetic, because they sustain a par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 63 publications
(140 reference statements)
0
39
0
Order By: Relevance
“…Previous studies have also suggested that the M06-2X functional sometimes underestimates magnetizabilities and ring-current strengths. 128 , 129 , 132 Revised versions of Minnesota functionals have been studied in this work and found to yield somewhat more accurate magnetizabilities than the original parameterizations. However, the revised versions also still appear on the second half of the ranking list.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also suggested that the M06-2X functional sometimes underestimates magnetizabilities and ring-current strengths. 128 , 129 , 132 Revised versions of Minnesota functionals have been studied in this work and found to yield somewhat more accurate magnetizabilities than the original parameterizations. However, the revised versions also still appear on the second half of the ranking list.…”
Section: Discussionmentioning
confidence: 99%
“…For carbon rings with different sizes, electronic properties including the gap between highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO), singlet‐triplet splitting, ionization potential, and electron affinity for cyclo[ n ]carbons ( n =10–100) were previously studied using thermally‐assisted‐occupation density functional theory (TAO‐DFT) [25] . Aromatic behavior and molecular magnetizability of some cyclo[ n ]carbons ( n up to 100) were also reported by Baryshnikov, Valiev, and their collaborators [26,27] . Optical properties, such as electronic absorption spectrum and (hyper)polarizability, are important molecular characteristics because they determine the possibility that molecules will eventually be used as practical optical materials.…”
Section: Methodsmentioning
confidence: 94%
“…and C 24 . 41 Furthermore, after the recent experimental generation of cyclo[18]carbon by Anderson and co-workers, 42 , 43 the aromaticity of cyclo[4 n + 2]carbons has gained increased attention, 39 , 44 yet these are outside our explicit focus herein.…”
Section: Introductionmentioning
confidence: 99%